The Role and Importance of Teachers in the Distance Learning System - Dobrić, Tamara; Đurić, Igor (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Distance learning is a planned learning that does not require the physical presence of students and teachers in one place, which means that they are spatially distant from each other. In distance learning, which is organized for both students and adults, the teacher is an indispensable participant. Teachers are expected to follow the innovations and better themselves in accordance with current changes in order to educate students to live in the current moment. A teacher who teaches at a distance should not only have educational, communicative, digital, methodical, and organizational skills but also high digital competence. Teachers` digital competencies are necessary for using modern educational technologies and distance learning. The digital competence enables teachers to work with modern information and communication technologies in order to achieve their goals in the context of their work.  It is of great importance that teachers have the ability to search for, gather, and critically analyse information, but also, skills to use multimedia information, the ability to access, search, and use the internet services needed for continuous professional development. The development of teachers` digital competencies today is necessary for the application of digital technologies in the educational process. The paper will discuss distance learning, educating teachers for distance learning as well as developing teachers` digital competencies. The aim of this work is to draw teachers` attention and enable them to realize specific characteristics of distance learning and to gain knowledge in the field of modern educational technologies, to keep improving permanently so as to apply the acquired knowledge in distance learning and therefore improve the educational process itself.
Keywords: distance learning; teacher; digital competencies of teachers